Comparative Study of Clinical Outcome of Low Pressure Versus Standard Pressure Pneumoperitoneum in Laparoscopic Cholecystectomy at Birat Medical College Teaching Hospital (BMCTH) - Sharma, Shivraj; Shrestha, Bhupendra Charan; Shah, Dhurba Narayan; Sharma, Ismita (Birat Journal of Health Sciences, 2023)
Introduction: Laparoscopic cholecystectomy at standard pressure pneumoperitoneum ( 12-15 mmHg of Co2) is standard of practice among surgeons. The increase in intraabdominal pressure by insufflation of carbon dioxide during laparoscopy brings certain changes in function of cardiopulmonary systems and also leads to postoperative pain due to stretching of the diaphragm. Objective: To minimise this impact on human physiology there is increasing effort of performing laparoscopic cholecystectomy at low pressure pneumoperitoneum (8mm Hg) however its safety has not been established. This study aims to compare outcomes of laparoscopic cholecystectomy at low pressure pneumoperitoneum versus standard pressure pneumoperitoneum in people undergoing laparoscopic cholecystectomy in terms of intraoperative time, postoperative pain including shoulder tip pain and length of hospital stay. Methodology: This descriptive randomised prospective study was conducted from Feb 2023 to Aug 2023 in the department of general surgery, BMCTH in patients diagnosed with symptomatic gallstone disease meeting inclusion criteria and willing for laparoscopic cholecystectomy. All patients were prospectively randomized into two groups randomly by the lottery method. A convenient sampling method was used. Group A odd number patients underwent surgery under low pressure (LPPLC group), Group B patients at standard pressure pneumoperitoneum (SPPLC). Results: A total of 145 patients (114 female and 31 male) with mean age 44.99 years of presentation. 73 patients underwent surgery under LPPLC group and 72 under SPPLC group. Mean pain recorded as per VAS score at 6, 12, 24 and 36 hours postoperatively showed no significant difference in pain among two groups with p value 0.972,0.121,0.212,0.072 respectively. Shoulder tip pain and additional need of analgesia was significantly less in LPPLC group, p value 0.002 and 0.015 respectively. No significant difference was observed in terms of operating time p value 0.151.Conversion between two groups p value 0.494 suggested no significant difference between two group. Conclusion: LPPLC is feasible, safe and can be considered over SPPLC. LPPLC is non inferior to SPPLC in terms of postoperative pain including shoulder tip pain and additional need of analgesia.